EFEKTIVITAS PEMBERIAN AROMATERAPI TERHADAP TINGKAT KECEMASAN IBU HAMIL TRIMESTER III - Tri Budi Rahayu (Bajang Institute, 2021)
Anxiety in pregnant women can arise especially in the third trimester of pregnancy, because during this period pregnant women feel anxious about various things such as normal or abnormal birth of the baby, the pain that will be felt, and so on [1]. One of the relaxation techniques to reduce anxiety is by giving aromatherapy. Aromatherapy is a complementary healing therapy to reduce anxiety by using aromatherapy essential oil scents. Aromatherapy used for individuals who experience anxiety is in the form of lavender aromatherapy. Lavender oil has a lot of potential because it has several ingredients such as monoterpenehydrocarbons, camphene, limonene, geraniol lavandulol. The design of this study is a literature review with a type of systematic literature review. Journals/articles that examine this research are published on Proquest, Pubmed, Garuda Portal, and Google Scholar. Of the 868 articles searched using predefined keywords, 9 articles met the inclusion criteria. Based on the results of a review of 9 articles, 8 articles stated that there was an effect of aromatherapy on the anxiety level of third trimester pregnant women and 1 article stated that there was no statistical evidence that strengthened the difference between aromatherapy and placebo on reducing anxiety levels in pregnant women